(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This study analyzes the transformation of art and design in the digital age, evaluating the impact of emerging technologies on creation, perception, and cultural consumption within commercial displays. The digital applications of these displays as scenographic spaces are explored, highlighting their role in the urban context. Additionally, immersive narratives and their influence on the viewer’s experience are examined. Technology redefines art and design, turning commercial displays into interactive spaces that actively engage the viewer. This phenomenon reinforces a society oriented toward consumerism and pleasures induced by digital media.